2017
DOI: 10.20344/amp.8606
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Acquired Urinary Tract Infections: Results of a Cohort Study Performed in an Internal Medicine Department

Abstract: 33% -48%) of which in the absence of clinical criteria for that procedure. The global cumulative incidence rate for nosocomial urinary tract infections was 4.6% (95% CI: 2.5% -6.7%). Most hospital acquired urinary tract infections (61.1%) were related to bladder catheter use. We quantified 3.06 infections / 1000 patient-days and 14.5 infections / 1000 catheter-days. Catheter associated urinary tract infection occurred at an early stage of hospitalization. The vast majority of patients (66.7%) that developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Therefore, it was very important to prevent and early detect urinary infection. Most nosocomial urinary infections were associated with indwelling urinary catheters, and its incidence could be significantly reduced by shortening indwelling time [ 11 ]. It was suggested to remove urinary catheter as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was very important to prevent and early detect urinary infection. Most nosocomial urinary infections were associated with indwelling urinary catheters, and its incidence could be significantly reduced by shortening indwelling time [ 11 ]. It was suggested to remove urinary catheter as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the perineal environment is not sterile. The guidelines of the American Society of Infectious Diseases and the British guidelines state that the use of disinfectant to clean the urethral opening in the absence of urinary tract infection is not recommended; however, the use of sterile saline to clean the urethral opening prior to surgery is recommended [7][8][9] . Studies have confirmed that adults or children who use or do not use disinfectant to clean the urethral orifice before induration show no statistically significant difference in the occurrence of urinary tract infection [10][11] .…”
Section: Discussion 41 the Use Or Non-use Of Disinfectant Before Separation Of Adhesions Of The Labia Minora Adhesion Has No Influence Onmentioning
confidence: 99%
“…must be considered as an important threat for progression of nosocomial UTIs among catheterized patients; hence, the catheters may act as an important source for aggregation of microbial pathogens, which are both antibiotic sensitive and antibiotic resistant. Thus, the use of assays pertaining to antibiotic susceptibilities and broad-spectrum antibiotics are pivotal items to reduce the number of patients with nosocomial UTIs [6,24,28].…”
Section: Predisposing Factors Relating To Urinary Tract Infectionsmentioning
confidence: 99%